2021
DOI: 10.3390/ani11092745
|View full text |Cite
|
Sign up to set email alerts
|

Pet–Human Relationships: Dogs versus Cats

Abstract: The study of human–animal interactions has increased, focusing on the dog–owner relationship, leaving a lag in research on the cat–owner relationship and practically a total absence of studies that compare the dog–owner relationship with the cat-owner relationship. Therefore, the objective of the present study was to make this comparison based on the perception of people living with both dogs and cats, considering interaction, emotional closeness, and perceived cost of the relationship. A total of 132 resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
1
14
0
13
Order By: Relevance
“…For these reasons, cat owners may not perceive their pets as an impediment to their daily outdoor activities, and this, in turn, may affect their perception of the costs of caring for the cat. Being aware of the cat’s social needs may lead to higher perceived costs in normal circumstances and to an even greater decrease in perceived costs during confinement than that observed in this study, similar to what has been previously found for dog owners [ 9 , 43 ]. However, we did not assess the degree of owners’ awareness of cats’ ethological and relational needs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For these reasons, cat owners may not perceive their pets as an impediment to their daily outdoor activities, and this, in turn, may affect their perception of the costs of caring for the cat. Being aware of the cat’s social needs may lead to higher perceived costs in normal circumstances and to an even greater decrease in perceived costs during confinement than that observed in this study, similar to what has been previously found for dog owners [ 9 , 43 ]. However, we did not assess the degree of owners’ awareness of cats’ ethological and relational needs.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, within the specific framework of the social exchange theory [ 41 ], the perception of the costs of caring for the pet may be affected by the (mis)beliefs and (mis)conceptions that owners may have of that species. Contrary to dogs, indoor cats are often wrongly considered capable of easily tolerating the absence of their owners, or [ 42 ] thriving even in small and confined spaces [ 43 ], with possible serious consequences for their welfare [ 44 , 45 , 46 ]. For these reasons, cat owners may not perceive their pets as an impediment to their daily outdoor activities, and this, in turn, may affect their perception of the costs of caring for the cat.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by González-Ramírez and Landero-Hernández [ 44 ] comparing the relationships between humans and dogs and humans and cats, the respondents indicated greater emotional closeness with their dogs than with cats (they noticed greater social support, companionship, and unconditional love in their dogs). The relationship of the owners with their cats was assessed as requiring less responsibility and associated with fewer restrictions in daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…We also found one quarter of individuals adopted a different species following return, most of whom returned a dog and adopted a cat. It is possible that individuals who returned dogs were more inclined to adopt cats post-return due to the lower perceived costs and responsibilities of cat ownership compared with dog ownership 21 .…”
Section: Discussionmentioning
confidence: 99%